Pop Art and the Critics - Mahsun, Carol Anne Runyon (Ann Arbor : UMI Research Press, 1987)
In lucid prose, Mahsun picks her way through the misconceptions, outraged outcries, vehement defenses and plain nonsense and leads us , first to a working definition of "Pop Art" and, then, to a clearer understanding of its legacy to the art world.
Notes p.125-133
Revision of author's thesis (Ph. D. - University of Chicago, 1981) originally presented under the title A review of the critical reactions to pop art in the United States
Bibliog. p. 135-141
Engels
boek
Keywords: Dine, Jim; Rosenquist, James; Johns, Jasper; Rauschenberg, Robert; Indiana, Robert; Oldenburg, Claes; Lichtenstein, Roy; Warhol, Andy; Segal, George; Wesselmann, Tom